Energy and economic optimization of a fishmeal plant using exergy analysis and experimental determination of mixture flows specific heat. - Gonzales Chávez, Salome (2015)
In this paper we formulate and apply the Exergy Analysis the set heat energy consumption elements of a typical plant of fishmeal, estimating experimentally the specific heat of the solid- liquid-vapor mixtures that form the raw material and steam, in order to optimize energy consumption by changes in the original installation and thus achieving the reduction in operating costs. Usually in these plants conventional energy balance and the premise that the specific heats are physical single phase flows is used; however, when solid-fat-water-steam mixture flows are presented, as is the case, these simple energy balances in each heating element become weak and lead to a high error margin in energy system assessment. In the methodology, the specific heats of mixture flows fat-water-vapor-solid is estimated by measurement of indicators in the industrial plant, contrasted with laboratory standards and empirical mathematical models. Then proceed to formulation and exergy calculation for each process and together, being elaborated a structured Excel program that calculates balances linked mass, energy and exergy. From this diagnosis suggestions for improvement are made to select the best alternative. As a result the best energy conformation of a typical fishmeal plant is obtained, this mean compared to the traditional system: excess fuel is removed, steam overproduction is removed and heat loss is reduced in each element. This represents an annual savings of ten million dollars plus additional benefits are presented as reduction of greenhouse gas emissions, effluents and improved industrial safety .